Efficacy assessment of bactericide containing dldecyldimethylammonium chloride on bacteria found in soak liquor at different exposure times - (:unkn) unknown (My University, 2010)
In this study, the efficacy of the bactericide containing didecyldimethylammonium chloride (quaternary ammonium compound) on the bacteria found in the main soak liquor at tannery was examined at different exposure times of 10 min., 30 min., 60 min., 120 min., 180 min., 240 min., 300 min., 360 min., 420 min. and 480 min. The presence of proteolytic and lipolytic mesophilic bacterial populations in high numbers in the main soak liquors showed that the recommended concentration of the bactericide (0.4 g/I) was not effective to control bacterial populations. Based on these results, the recommended concentration of the bactericide in the main soaking process was doubled (0.8 g/1) and it was observed that this concentration was considerably effective in controlling the bacterial growth. In addition, the bacterial flora in the main soak liquor treated with this bactericide was examined. Enterobacter gergoviae, Enterobacter sakazakii, Enterobacter amnigenus biogrup I, Enterobacter cloaceae, Pseudomonas fluorescens, Pseudomonas luteola, Pseudomonas aeruginosa, Pseudomonas put ida, Enterococcus avium, Enterococcus faecium, Lactococcus lactis ssp. lactis, Aerococcus viridans, Vibrio parahaemoiyticus, Kocuria varions, Staphylococcus hominis, Staphylococcus capitis, Staphylococcus sciuri, Staphylococcus xylosus, Staphylococcus cohnii ssp. urealyticus, Staphylococcus epidermidis, Staphylococcus intermedius. Staphylococcus haemolyticus, Staphylococcus lugdunensis, Staphylococcus cohnii ssp. cohnii. Staphylococcus warneri and Micrococcus spp. were isolated and identified from the main soak liquor after doubling the bactericide concentration. As a conclusion, the recommended dose of commonly used bactericides should be tested periodically in main soaking process at tanneries to inactivate various bacterial populations found in soak liquors.